Disease course heterogeneity and OCT in multiple sclerosis. (August 2014) - Balk, LJ; Tewarie, P; Killestein, J; Polman, CH; Uitdehaag, BMJ; Petzold, A
Background: The heterogeneity of the disease course in multiple sclerosis (MS) remains a challenge for patient management and clinical trials. Objective: The objective of this paper is to investigate the relationship between disease course heterogeneity and retinal layer thicknesses in MS. Methods: A total of 230 MS patients and 63 healthy control subjects were included. Spectral-domain OCT scanning of the peripapillary and macular regions was performed, followed by automated eight-layer segmentation. Generalised estimation equations were used for comparisons. Receiver operating characteristic (ROC) curves were calculated for distinguishing a benign from a typical disease course. Results: Primary progressive patients showed relative preservation of inner retinal layers, compared to the relapsing onset MS types. Only in MS eyes without optic neuritis did patients with typical MS show more severe thinning of the inner retinal layers (RNFL to INL) compared to patients with a benign disease course, even after an average disease course of 20 years. Conclusion: The thicknesses, particularly of the innermost retinal layers (RNFL, GCC), were significantly related to the heterogeneous disease course in MS. The relative preservation of these layers in primary progressive and benign MS suggests rather limited susceptibility of the retina to neurodegeneration, which may be relevant for future neurodegenerative treatment trials employing OCT as a secondary outcome measure in primary progressive MS.